Pembatasan Dan Pengalihan Tanggung Jawab Bank Penerbit Atas Produk Uang Elektronik: Perspektif Hukum Ekonomi Syariah - Sulistyowati, Diyah; Zaenul Fuad, Iwan; Ilham, Muhammad (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2024)
This research aims to analyze the validity and impact of restrictions and transfer of responsibility of e-money issuing banks on consumer legal protection. This research uses empirical legal research methods with two sources of research data. Primary data sources are obtained from general provisions on Brizzi electronic money products issued by BRI and secondary data sources are taken from books, journals, research results, or others. The data analysis technique uses descriptive analysis techniques. The results of this study indicate that the general provisions made by BRI are valid and binding on BRI and consumers who promise in the general provisions. The application of restrictions and transfer of responsibility by BRI is in line with binding regulations, so that these general provisions provide legal certainty for the parties involved. In terms of legal protection, BRI is responsible for transaction security, but BRI does not bear losses due to card loss as agreed in the general conditions. This is in accordance with the principles of electronic money in sharia economic law, namely the principles of justice and responsibility. This research contributes to scientific development, especially regarding aspects of consumer protection in electronic-based financial transactions.